THE INFLUENCE OF LEADERSHIP AND THE SYSTEM APPRECIATION OF WORK MOTIVATION AND PERFORMANCE - Ummu Hanik; Imam Suroso; Muhaimin Dimyati (STIE Mandala Jember, 2018)
This research aims to know and analyze the influence of leadership and the awardsystem to performance through work motivation. The subjectsof this research are theemployees of Technical Implementation Unit for Services Revenue East Java province allordinate of Probolinggo that consist of 77 people.This research uses explanatory research. As the independent variable is leadership (X1)and award system (X2), the intervening variableis work motivation (Y1), and thedependent variable is performance (Y2). Analyses of the data used are validity andreliability, the classic assumption test, the suitability of the model test and path analysis.The result shows that the leadership has a significant effect on work motivation, rewardsystems have a significant effect on work motivation, leadership does not significantlyinfluence the performance, reward systems have a significant effect on performance, andwork motivation has significant effect on performance.The coefficient of determination (R2) for path model is 0.9841 or 98.41% in the form of apercentage. It means the diversity of data that can be explained in this study is 98.41%.The information contained in the data amounted to 98.41% can be explained by the pathmodel. While the rest of 1.59% are explained by other variables which arenot examinedin this study.